Is the EU ready for the next generation of investment? The case of France and Germany - Alberto Nonnis; Felix Roth; Ahmed Bounfour (University of Hamburg, Department of Economics, Senior Lecturer in International Economics, 2024)
This paper presents a puzzling finding: although France invests twice as much in intangible capital vis-à-vis Germany, both countries have similar LPG rates over the studied period from 1995 until 2020. We find that this difference in investments is driven by France's four- and two-and-a-half-fold investments in software and organizational capital. Our paper offers three perspectives to clarify the puzzle. First, higher investments in intangible capital in France might suggest a better readiness of the country towards the next generation of investment. However, France's investments in intangibles appear to be less efficient compared to those of Germany. Third, measurement problems in the software and organizational capital investment series are also to be considered to understand this major puzzle.
Keywords: 330; Intangible capital; Labour Productivity; Germany; France; EU